2012
DOI: 10.1371/journal.pntd.0001569
|View full text |Cite
|
Sign up to set email alerts
|

Glycotope Sharing between Snail Hemolymph and Larval Schistosomes: Larval Transformation Products Alter Shared Glycan Patterns of Plasma Proteins

Abstract: Recent evidence supports the involvement of inducible, highly diverse lectin-like recognition molecules in snail hemocyte-mediated responses to larval Schistosoma mansoni. Because host lectins likely are involved in initial parasite recognition, we sought to identify specific carbohydrate structures (glycans) shared between larval S. mansoni and its host Biomphalaria glabrata to address possible mechanisms of immune avoidance through mimicry of elements associated with the host immunoreactivity. A panel of mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 50 publications
3
32
0
Order By: Relevance
“…Several recent studies (Lehr et al, 2010; Yoshino et al, 2012, 2013) have shown that S. mansoni miracidia and sporocyst surface proteins and sporocyst transformation products bear glycan structures that are similar to those found expressed on plasma proteins or hemocytes of B. glabrata . This similarity adds significant additional evidence to a long-standing hypothesis (Damian, 1964) that parasites may escape immunological detection in their hosts by molecular mimicry.…”
Section: What Is the Mechanistic Basis Of Digenean Specificity Formentioning
confidence: 87%
See 2 more Smart Citations
“…Several recent studies (Lehr et al, 2010; Yoshino et al, 2012, 2013) have shown that S. mansoni miracidia and sporocyst surface proteins and sporocyst transformation products bear glycan structures that are similar to those found expressed on plasma proteins or hemocytes of B. glabrata . This similarity adds significant additional evidence to a long-standing hypothesis (Damian, 1964) that parasites may escape immunological detection in their hosts by molecular mimicry.…”
Section: What Is the Mechanistic Basis Of Digenean Specificity Formentioning
confidence: 87%
“…This similarity adds significant additional evidence to a long-standing hypothesis (Damian, 1964) that parasites may escape immunological detection in their hosts by molecular mimicry. Further support for this idea comes from the observation that plasma proteins from susceptible strains of B. glabrata have a greater distribution and abundance of sharing of some glycans than plasma proteins from a schistosome resistant strain (Yoshino et al, 2012). This may in turn enable non-self detecting molecules circulating in snail plasma, including the diverse FREP plasma proteins (Zhang et al, 2004), to recognize sporocysts more readily in resistant snails.…”
Section: What Is the Mechanistic Basis Of Digenean Specificity Formentioning
confidence: 99%
See 1 more Smart Citation
“…Larval glycans and/or their associated glycoconjugates might also be serving as PAMPs that interact with lectin-like PRRs (284). PRRs, such as Toll receptors, C-type lectins, galectins, nucleic acid-sensing receptors, and the intracellular nucleotide-binding oligomerization domain (NOD)-like receptors (NLRs) occur both extracellularly and intracellularly, with the galectins notably found in both the cytoplasm and extracellularly (285).…”
Section: Glycan Interactions With Intermediate Hostsmentioning
confidence: 99%
“…During their development in the molluscan intermediate host, S. mansoni sporocysts release excretory/secretory glycoproteins that bind to lectin PRRs on the surface of the snail host hemocytes and are believed to modulate the ability of the hemocytes to interact with the developing larvae (279). The binding of glycoconjugates to B. glabrata hemocyte lectins can trigger the generation of parasite-killing reactive oxygen species, thereby mediating innate immune responses to invading miracidia (10, 275, 277, 280, 281, 284). …”
Section: Glycan Interactions With Intermediate Hostsmentioning
confidence: 99%